2005
DOI: 10.1016/j.femsle.2004.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Transformation ofConiothyrium minitans, a parasite ofSclerotinia sclerotiorum, withAgrobacterium tumefaciens

Abstract: Coniothyrium minitans is a potential biological control agent of the plant pathogenic fungus Sclerotinia sclerotiorum. In this research, T-DNA insertional transformation of strain ZS-1 of C. minitans mediated by Agrobacterium tumefaciens was obtained, with optimization of spore maturity for transformation. After confirmation by PCR, transformants were subjected to Southern blot analysis, and results showed that more than 82.7% of transformants had single T-DNA insertions, and 12.1% of transformants had two cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 22 publications
(30 reference statements)
1
57
0
1
Order By: Relevance
“…Huang et al(2015) also used a different mutagen, which may have been more effective than EMS. Other effective mutagens, which have previously been used with considerable success in fungi are gene tagging by direct DNA transfer (Seong et al, 2005), restriction enzyme mediated integration (REMI) (Brown et al, 1998), Agrobacterium mediated T-DNA (Li et al, 2005) and transposon insertions (Firon et al, 2003). However, in some cases, these mutagens can induce chromosomal rearrangements and/or multiple insertions (Brown et al, 1998;Chung et al, 2003), causing difficulties in determining the causative mutation behind an observed phenotype (reviewed in Weld et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al(2015) also used a different mutagen, which may have been more effective than EMS. Other effective mutagens, which have previously been used with considerable success in fungi are gene tagging by direct DNA transfer (Seong et al, 2005), restriction enzyme mediated integration (REMI) (Brown et al, 1998), Agrobacterium mediated T-DNA (Li et al, 2005) and transposon insertions (Firon et al, 2003). However, in some cases, these mutagens can induce chromosomal rearrangements and/or multiple insertions (Brown et al, 1998;Chung et al, 2003), causing difficulties in determining the causative mutation behind an observed phenotype (reviewed in Weld et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…RNA samples were treated with DNase I (RNase Free) before use. Southern and Northern blot analyses were conducted as described previously (19,42).…”
Section: Methodsmentioning
confidence: 99%
“…To test the possible transmission of hypovirulence and SsHADV-1 from strain DT-8 to a vegetatively incompatible virulent strain (Ep-1PNA367), strain Ep-1PNA367 was labeled with the hygromycin B resistance gene (hph) using Agrobacterium-mediated transformation as described by Li et al (42). The transmission test between DT-8 and labeled Ep-1PNA367 (named strain Ep-1PNA367 R ) was conducted using the method described by Zhang et al (40).…”
Section: Methodsmentioning
confidence: 99%
“…Fungi that have been recalcitrant to transformation by other systems have been successfully transformed by co-cultivation with Agrobacterium [27]. AMT is a relatively simple system to work with, does not require the production of protoplasts, and is suitable for both gene-replacement by homologous recombination [1,28,29] and insertional mutagenesis by random integration [30,31].…”
Section: Achieving Stable Homokaryotic Transformationmentioning
confidence: 99%
“…T-DNA tagging has been used successfully to find new genes [30,70] and T-DNA tagging projects on fungi have recently been initiated in many laboratories around the world [31,68]. AMT is very suitable for insertional mutagenesis as it can cause a relatively high frequency of transformation [71][72][73] and often creates single-copy integrations [27,31].…”
Section: T-dna Taggingmentioning
confidence: 99%